N-Cyclohexylbenzamide - Khan, I.U.; Javaid, R.; Sharif, S.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The structure of the title compound, C(13)H(17)NO, features an anti disposition of the N-H and carbonyl groups. The amide group is twisted with respect to the benzene ring [N-C(= O)-C-C torsion angle = -30.8 (4) angstrom]. In the crystal, C(4) chains propagating in [100] are formed by intermolecular N-H center dot center dot center dot O hydrogen bonds. Weak C-H center dot center dot center dot pi interactions link the chains into sheets.